The Role of Reforms in the Field of Spirituality in the Development of the Society of New Uzbekistan - Kuyliyev Tulkin; Rakhmonberdiyeva Nadira (Miasto Przyszłości, 2023)
The main principle of the beginning and development of spiritual and educational reforms in the new Uzbekistan is the consistency and continuity of this process. This article analyzes the forms and features of the manifestation of spiritual values during the renewal of our country and their impact on the social life of our society. The article also analyzes the fact that the concept of spiritual reforms put forward in the Address of the President of the Republic of Uzbekistan Shavkat Mirziyoyev to the country's parliament is consistent from a scientific and theoretical point of view and reflects continuous activity from a practical point of view. view. This article discusses the forms and features of the manifestation of threats in the process of globalization and their negative impact on the social life of our society.